FACTORS INFLUENCING THE ADOPTION OF ONLINE INSURANCE PRODUCTS - Mst. Samanta Nasrin (International Journal of Accounting, Finance and Business, 2022)
This study investigates the influence of consumer traits on the number of insurance products adopted by consumers. We empirically examine the relationships between these variables using data from 509 consumers collected through an online survey. The results suggest that consumers with low social needs, are price-conscious, and perceive fewer risks when buying on the Internet tend to purchase more online insurance products. We discuss the managerial implications of our findings to increase the effectiveness of marketing efforts.